Grading Bias and Young Adult Mental Health - Anna Linder; Martin Nordin; Ulf-G. Gerdtham; Gawain Heckley (Lund University, School of Economics and Management, Department of Economics, 2022)
Various grading reforms and trends of more lenient grading have contributed to grade inflation in Sweden and other countries. Previous research shows that over-grading increases higher education enrolment, achievements and earnings, but no study has yet addressed the potential impact of grading bias on health. In this paper, we hypothesize that over-grading has a protective impact on mental health, either through a direct effect of performance feedback, or through mechanisms such as self-efficacy and university admission distortions. We test this hypothesis using Swedish individual-level register data for individuals graduating from upper secondary school in the years 2001-2004. Grading bias, which we interpret as over-grading, is constructed as the residual of final upper secondary school grades having controlled for results in a standardised test, itself not subject to grading leniency. Over-grading is further isolated by considering only within-school variation in over-grading and controlling for prior grades and school production. We show that over-grading has substantial significant protective impacts on the mental health of young adults, but only among female students. That grades themselves, independent of knowledge, substantially impact the production of health highlights an important health production mechanism, and also implies that any changes to the design of grading systems must consider these wider health implications.
Keywords: I10; I21; I28; 330; Grading bias; grade inflation; mental health; human capital development